Le manuel scolaire : Au-delà de l'outil pédagogique, l'objet politico-social - Atfa Memaï; Abla Rouag
The school textbook is an essential vector of instruction and socialization, it is the bearer of knowledge, but also of norms and values. The purpose of this article is to go beyond the pedagogical issues of the textbook, to highlight its political, ideological and sociological implications.